Sinergi Kolektif : Urgensi dan Strategi Penguatan Kerja Tim dalam Meningkatkan Mutu Kelembagaan di Madrasah Ibtidaiyah - Ima Rosila; Ria Ratna Ningtyas; Ahmad Ta’rifin; Elis Nursetialloh; Khasan Nuzaki (Lembaga Pengembangan Kinerja Dosen, 2026)
Teamwork is a fundamental element and a strategic pillar in the governance of educational institutions, particularly at the Madrasah Ibtidaiyah (MI) level, which demands the integration of religious values and national academic standards. This article aims to deeply analyze the urgency of team formation, the dynamics of the effective team-building process, and strategies for maintaining team cohesion to support the success of Islamic primary education organizations. This research employs a descriptive qualitative approach through literature reviews and in-depth interviews with a limited number of informants competent in madrasah management. Through the analysis of literature and field data, it was found that the urgency of teamwork in MI lies not only in administrative efficiency but also in creating an adaptive and collaborative learning environment. The results indicate that a solid work team significantly enhances the quality of learning through the exchange of ideas between teachers and staff, strengthens internal coordination systems often hindered by bureaucracy, and optimizes human resource development through knowledge transfer among members. Furthermore, this study identifies three main pillars for successful teamwork in MI: first, participative leadership capable of embracing all aspirations of the madrasah community; second, open communication that minimizes internal conflict; and third, clear task distribution based on individual competence (the right man on the right place). These findings provide practical implications for madrasah heads to prioritize a collective work culture over individualistic efforts to achieve accreditation targets and a vision of superior Islamic education in the contemporary era.